2006
DOI: 10.1017/s0022029905001676
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and nature of electrochemical activity in milk from a herd of dairy cows

Abstract: Amperometric sensors may be used in milk analysis but electrochemical interference from compounds other than the analyte is an on-going problem. A survey was made of the level of electrochemical activity (potential interference) in milk from a herd of dairy cows grazing on summer pasture. It was a ubiquitous feature of the aqueous phase of whey and de-proteinized milk over about 3 months. The nature of the interference was studied by differential pulse voltammetry and responses to ascorbic acid oxidase and uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The relative standard deviation (STD) for all measurements placed within the limit for reliable measurements (RSD < 5%) [26,27]. These results validate that the procedure is suitable for the development of a sensitive and reproducible aptasensor.…”
Section: Resultsmentioning
confidence: 66%
“…The relative standard deviation (STD) for all measurements placed within the limit for reliable measurements (RSD < 5%) [26,27]. These results validate that the procedure is suitable for the development of a sensitive and reproducible aptasensor.…”
Section: Resultsmentioning
confidence: 66%
“…The response of the CDH modified SPCEs as a function of pH showed that the response current for both immobilised enzymes attained a maximum at pH 4.5 (citrate buffer containing 0.1 M KCl), that was used in the following experiments. In order to minimise enzyme inactivation, possible interferences from other components, which might be present in the sample (e.g., ascorbic, uric acids) [29][30][31][32] but, on the other hand, still be able to detect the analyte with a high sensitivity a potential of 100 mV vs. pseudo Ag|AgCl (which is formed on the surface of the reference electrode due to the presence of KCl in the working buffer) was chosen for all further experiments. A flow rate of 0.57 mL min −1 provided a good combination of both high and rapid analytical response for the chosen system and was used for further experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of lactose with biosensors sometimes requires pre-treatment of milk samples to remove fat and proteins [16]. The response of a lactose biosensor may be additionally affected by calcium chloride, ascorbic and/or uric acids [17].…”
mentioning
confidence: 99%